A Study of Nutritional Status of Children Attending Anganwadi Centres of a District in Central India - Anil Singh Baghel; Saket Kale; Arpit Verma; Sanjay Kumar Chourasiya (Medsci Publications, 2018)
Introduction: The burden of under-nutrition among children has not changed much even though various intervention programs are in operation in India. The study was conducted to assess the mag- nitude of under nutrition among children under 6 year of age and to study factors associated with under-nutrition of selected chil- dren. Material & Methods: This community based cross sectional study had utilized two stage sampling technique. Sample size was de- termined by the use of formula 4pq/l2. In first stage, selection of anganwadi centers (AWC) was done by using simple random sampling method. In second stage, children were selected from se- lected AWCs. Result: Out of total 380 children 192 boys and 188 were girls. 180 (47.4%) children were under nutrition out of which 99 (55%) chil- dren were of grade I, 62(34.4) were grade II and 19 (10.6%) chil- dren were of grade III as per the Indian Association of Pediatrics (IAP) classification of under nutrition. Conclusion: Among the factors studied, educational status of mother and socio-economic status of family were most strongly associated with the under nutrition.